Do FOMC members herd? - Jan-Christoph Rülke; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Twice a year FOMC members submit forecasts for growth, unemplyoment and in ation to be published in the Humphrey-Hawkins Report to Congress. In this paper we use individual FOMC forecasts to assess whether these forecasts exhibit herding behavior, a pattern often found in private sector forecasts. While growth and unemployment forecast do not show herding behavior, the in ation forecasts show strong evidence of anti-herding, i.e. FOMC members intentionally scatter their forecasts around the consensus. Interestingly, anti-herding is more important for nonvoting members than for voters.
Keywords: E43; E52; E27; 330; Federal Open Market Committee; monetary policy; forecasting; herding; Geldpolitik; Gruppenentscheidung; Wirtschaftsprognose; Herdenverhalten; USA